The utilization of the "shake and take" learning media in introducing one to one corespondence in group B Paud Al Bunyamur Kemayoran Jakarta Pusat - Ningsih, Silvia (Educenter : Jurnal Ilmiah Pendidikan, 2022)
In introducing one-to-one correspondence using media in group B at PAUD Al Bunyamur Kemayoran, Central Jakarta, the aim is to understand the concept of numbers and children feel learning while playing. The time of observational research was carried out in December 2020 to May 2021. This type of research was classroom action research which was carried out in two cycles. The subjects in the study were students in group B at PAUD Al Bunyamur Kemayoran, Central Jakarta, totaling 15 children. The data obtained were taken from observation sheets and documentation. Analysis of research data used qualitative and quantitative approaches which were analyzed descriptively. The results showed that the use of "shake and take" media in explaining one-to-one correspondence could understand the concept of numbers. After taking action shows a change for the better. In the first cycle, it increased to 33.33% with the category developing as expected. And in the second cycle there was a significant increase to 83.33% with a very well developed category. It can be concluded that through the use of "shake and take" media in explaining one-to-one correspondence, one can understand the concept of numbers.